Kualitas Pelayanan Program Mobil Konseling Denpasar Ceria pada Dinas Pemberdayaan Masyarakat dan Desa Kota Denpasar - Nuryanti, Ana Dwi; Supriliyani, Ni Wayan; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2021)
The Denpasar City Government through the Denpasar City Community and Village Empowerment Service provides free counseling services to the community in a program called "Mobil Konseling Denpasar Ceria". This service is a place for the community to share their problems and keep their secrets safe. The purpose of this study was to determine the quality of service in the Mobil Konseling Denpasar Ceria Program. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results showed that the service quality of the Mobil Konseling Denpasar Ceria Program is still not running optimally. There are several obstacles in its implementation, such as the unavailability of a forum for community aspirations for online service users, inconvenient use of services via WhatsApp messengers, and not yet optimal socialization of services to the community.